A inserção de metodologias ativas na formação inicial de professores de química: possibilidade e desafios - Pereira, Vanessa Teixeira (2023)
In the literature in Science Teaching, there is little research that reports results from the inclusion of active methodologies in Chemistry Degree courses, despite their potential in promoting innovative experiences for the didactic-pedagogical training of future teachers. In this sense, the present study aims to investigate the contributions of participation in and planning classes with a case or problem. To this end, a sequence of classes structured around the principles of the Flipped Classroom was implemented, to provide chemistry teachers in training with the opportunity to come into contact with the theoretical foundation of active methodologies and the experience of experiencing teaching activities based on the Study of Cases and Problem-Based Learning. This research has a qualitative character and was developed in the discipline of Teaching Practice in Chemistry III of the Chemistry Degree Course at the Chemistry Institute of the Federal University of Mato Grosso do Sul. The data collection instruments were the initial and final questionnaires, recording on audio of presentations, lesson plans, and written productions carried out by undergraduate students during the development of the proposed activities. The results indicate that there was a notable evolution of graduates as activities progressed, and they gradually became more active and autonomous. The work carried out in groups stimulated debate among them, teamwork, critical and reflective positioning and the sharing of knowledge. Therefore, the experience that undergraduates had with active methodologies and the development of lesson plans from the perspective of these methodologies contributed to reflective, active and autonomous training.